Meiofauna communities' response to an anthropogenic pressure: The case study of green macroalgal bloom on sandy beach in Brittany. (31st October 2019) - Baldrighi, Elisa; Grall, Jacques; Quillien, Nolwenn; Carriço, Rita; Verdon, Valentin; Zeppilli, Daniela
Abstract: Open sandy beaches support key ecological functions and a distinctive biodiversity, but are threatened by an increasing anthropogenic pressure. Among these threats is the occurrence of green tides of Ulva spp., expression of the eutrophication phenomenon. Our study aimed at determining the impact of green macroalgal accumulations on benthic meiofauna inhabiting two macrotidal sandy beaches of Brittany: Saint Nic (impacted) and Anse de Dinan (unimpacted). The presence of Ulva enhanced total meiofaunal abundance and nematode functional diversity when compared to a state free from macroalgal mats. The stranded Ulva supported high values of meiofaunal β-diversity as well. This unexpected response was likely due to the highly dynamic nature of open sandy beaches that prevents O2 depletion within sediments. Natural seasonal changes in meiofaunal biomass and composition were also evident at both beaches and changes in environmental features, apart from eutrophication alone, do drive the variability in meiofaunal biomass and nematodes diversity. Highlights: The presence of Ulva at open sandy beaches enhances total meiofaunal abundance. Stranded Ulva supports a high nematode functional diversity. Ulva mats promote high values of meiofaunal β-diversity. Natural seasonal changes in meiofauna communities are also evident. The intermediate disturbance model well explains the meiofauna response to Ulva mats.